GREEN AND EFFECTIVE SYNTHESIS AND CHARACTERIZATION OF IMINO CHROMENE PRODUCTS WITH EVEN ALKYL TAIL - Madasamy Kumar, Veerappan Jeyachandran (International Journal of Modern Agriculture, 2020)
The reaction between substituted 4-hydroxy benzaldehyde, active methlyene compounds and/or resorcinol yield imino chromene derivatives. Structures of these were established upon the basis of IR, 1HNMR, 13CNMR, and MASS data.